DEFINING WEIGHTING MATRICES ON OPTIMAL TRACKING CONTROL USING ADAPTIVE PARTICLE SWARM OPTIMIZATION - Mu'tamar, Khozin
In this manuscript, we present an approach for selecting appropriate weighting matrices for optimal tracking control design using adaptive particle swarm optimization (APSO), applied to landing flare system. First, we develop a linearized state space model based on longitudinal motion of aircraft. Next, based on LQR, controller for optimal tracking is developed. APSO is used to improve control performance by selecting appropriate weighting matrices. APSO is modified standard PSO which have multi global best that weighted using Mamdani fuzzy model. Simulation is given to illustrate the design procedure and to show comparation of tracking performance between APSO and standard PSO.